1999
DOI: 10.1159/000016900
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgical Techniques for the Treatment of Gastroesophageal Reflux Disease

Abstract: Open antireflux surgery produces good long-term control of disease, but new interest in the surgical management of gastroesophageal reflux disease has been stimulated by the introduction of minimally invasive techniques to perform standard antireflux procedures. In the past some scepticism existed among gastroenterologists who quoted the poor surgical results they had seen. These bad results, however, were largely due to inappropriate surgery in poorly worked-up patients or antireflux surgery performed by inex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Other published studies have shown excellent results with 5-year follow-up. 10 Even within the learning curve, the patient satisfaction is quite high and this is likely to remain the same or even improve as the surgeon gains more experience. Our conversion rate of 23.6% during the learning curve compares quite favourably with other published series from North America and Australia 5,11,12 all of which reported a conversion rate of 20% for the first 100 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies have shown excellent results with 5-year follow-up. 10 Even within the learning curve, the patient satisfaction is quite high and this is likely to remain the same or even improve as the surgeon gains more experience. Our conversion rate of 23.6% during the learning curve compares quite favourably with other published series from North America and Australia 5,11,12 all of which reported a conversion rate of 20% for the first 100 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of laparoscopy in the late 1980s marked a milestone in surgery. Its advantages of diminished pain, surgical wound complications, hospital stay and global costs in uncomplicated cases of gallbladder disease (Gadacz 2000) led to the expansion of its use to other intra-abdominal organs such as the distal oesophagus, the proximal stomach (Chekan 1999;Consensus 1997;Horgan 1997;Klingler 1999) and the colon (Rickard 2001;Tisminezky 2000).…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Because many cases of rGERD involve mechanical failure, such as hiatal herniation, slippage of the wrap, or wrap dehiscence [10,13,[28][29][30][31][32][33][34][35], factors that might relate to impaired healing and increased mechanical stress were also investigated. These included systemic factors that might impair healing, such as nutritional status and steroid use.…”
Section: Definitions and Selection Of Potential Risk Factorsmentioning
confidence: 99%